2020
DOI: 10.1021/acs.analchem.9b05604
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship Between H2O2 and HClO in Living Cells by a Bifunctional, Dual-ratiometric Responsive Fluorescent Probe

Abstract: As two important reactive oxygen species, hydrogen peroxide (H 2 O 2 ) and hypochlorous acid (HClO) play vital roles in many physiological and pathological processes. However, the relationship between these two species is seldom investigated, in part, because of the lack of robust molecular tools that can simultaneously visualize HClO and H 2 O 2 in biosystems. In this work, we present a design strategy to construct a single fluorescent probe that can detect H 2 O 2 and HClO by simultaneously monitoring two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…6 Han et al constructed a multifunctional uorescent probe capable of detecting H 2 O 2 and cholesterol by simultaneously monitoring two different detection channels. 7 We found that both Sn(II) and AA can reduce Fe(III) to Fe(II) without further reducing Fe(II) to Fe, so the platform designed by us can be used to detect Sn(II) and AA.…”
Section: Introductionmentioning
confidence: 87%
“…6 Han et al constructed a multifunctional uorescent probe capable of detecting H 2 O 2 and cholesterol by simultaneously monitoring two different detection channels. 7 We found that both Sn(II) and AA can reduce Fe(III) to Fe(II) without further reducing Fe(II) to Fe, so the platform designed by us can be used to detect Sn(II) and AA.…”
Section: Introductionmentioning
confidence: 87%
“…Wang’s group constructed a dual-ratiometric fluorescent probe (example 18) that can simultaneously detect HClO and H 2 O 2 by two channels ( Figure 23 ). 20 In probe 18, coumarin was the fluorescent parent, and the recognition group of HClO and H 2 O 2 was skillfully combined. The probe had high selectivity and sensitivity to H 2 O 2 and HClO and meanwhile could be used to monitor the generation of endogenous H 2 O 2 and HClO.…”
Section: Dual-function Fluorescent Probesmentioning
confidence: 99%
“…Fluorescent probes have been widely used in ClO À fluorescence imaging in recent years due to their advantages of simplicity, high sensitivity, high selectivity and real-time monitoring. [13][14][15][16][17][18][19][20][21][22] Various fluorophores used to design ClO À fluorescent probes mainly include coumarin, [23][24][25] rhodamine, [26][27][28] cyanine, [29][30][31] 1,8-naphthalimide [32][33] and boron-dipyrromethene (BODIPY). [34][35] Among them, BODIPY is often used in the design of in vivo imaging probes due to its excellent photostability, low cytotoxicity, polarity and pH insensitivity, and chemical robustness.…”
Section: Introductionmentioning
confidence: 99%